1981
DOI: 10.1161/01.hyp.3.6_pt_2.ii-14
|View full text |Cite
|
Sign up to set email alerts
|

Renin-like activity in the rat brain during the development of DOC-salt hypertension.

Abstract: SUMMARY Lerels and distribution of an angiotenslD-fonning enzyme, active at the physiological pH (isorenin), were determined in the central nervous system of 24 rats treated with 25 mg/kg of deoxycorticosterone (DOC) subcutaneously, twice a week, plus saline to drink during 30 days, and in 14 control animals. Different areas of the brain were excised and homogenized. Renin activity and concentration were determined by incubation of the supernatant of each homogenate at pH 7.2 alone and in the presence of an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
2
21
0
2
Order By: Relevance
“…Furthermore, Wilson et al (27) have demonstrated that the number of angiotensin II binding sites is increased following treatment with mineralocorticoids, even in neuronal cell preparations from brain tissues. In addition, it has been reported that DOCA-salt hypertensive rats show elevated central renin activity (28). In the present study, the pressor response to angiotensin II injection into the AHA was enhanced in DOCAsalt hypertensive rats as compared with that in shamoperated rats.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, Wilson et al (27) have demonstrated that the number of angiotensin II binding sites is increased following treatment with mineralocorticoids, even in neuronal cell preparations from brain tissues. In addition, it has been reported that DOCA-salt hypertensive rats show elevated central renin activity (28). In the present study, the pressor response to angiotensin II injection into the AHA was enhanced in DOCAsalt hypertensive rats as compared with that in shamoperated rats.…”
Section: Discussionsupporting
confidence: 51%
“…After DOCA-salt treatment for 1 month, renin-like activity and Ang II in hypothalamus and brain stem nuclei were elevated, but plasma renin activity was very low (7,8). In rats with DOCA-salt hypertension for 4-8 weeks, angiotensin II receptor binding on autoradiography was also elevated in selected brain areas involved in cardiovascular regulation, such as nucleus of solitary tract, area postrema, median preoptic nucleus, subfornical organ, and solitary vagal area (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…DOCA-salt-treated rats show higher Ang II receptor density in brain areas involved in cardiovascular regulation, such as the nucleus of solitary tract, area postrema, median preoptic nucleus, subfornical organ, and solitary vagal area (4)(5)(6), and have elevated levels of renin and Ang II in hypothalamus and brain stem nuclei (7,8). Acute intracerebroventricular (icv) administration of captopril decreases the blood pressure of DOCA-salt hypertensive rats (9).…”
Section: Introductionmentioning
confidence: 99%
“…14 ' 15 There is also evidence that brain Ang II may be involved in the deoxycorticosterone acetate (DOCA)-salt model of hypertension. Although plasma renin activity is depressed in DOCA-salt hypertensive rats, 16 DOCA-salt rats have elevated brain renin activity 17 and increased responsiveness to intracerebroventricular Ang II. 18 The increased responsiveness to intracerebroventricular Ang II is consistent with the demonstration that binding of 12S I-[Sar']Ang II is also elevated in the brains of DOCA-salt rats.…”
Section: Angiotensin N Receptors In the Solitary-vagal Area Of Hypertmentioning
confidence: 93%